Urban Water Management for Future Cities Technical and Institutional Aspects from Chinese and German Perspective - Köster, Stephan; Reese, Moritz; Zuo, Jian'e (Future City, 2019)
This book features expert contributions on key sustainability aspects of urban water management in Chinese agglomerations. Both technical and institutional pathways to sustainable urban water management are developed on the basis of a broad, interdisciplinary problem analysis.